Upaya Pemerintah Menghadapi âInvasiâ Produk China Mulai 1 Januari 2010 - Hanantijo, Djoko (Responsibilitas, 2010)
Abstract FTA would be of benefit to a state because giving efficiency expense of transfer of goods through integration process of political economy line in an area. But, FTA has available prerequisite of enough infrastructure. Various governmental efforts since Infrastructure Summit I and II until initial Investment Summit of December 2009 has not given result is gratifying. Infrastructure still becoming discourse. Electrical crisis and height of expense of arranging commercial to become some of problems which cannot be disregarded. Independence of exploiting economics of local potency for domestic and export earns is optimal and gives maximum economics benefit. Readiness Of Indonesia faces FTA is expected to brings success for Indonesia. The success is marked with Indonesia export activity that is increasingly active and increases itâs the volume. But, sees government effort assessed has not is optimal hence fear of business perpetrator would continuously increase. Keyword: FTA, produk cina.